Pengembangan Sistem Marketplace Tanah dan Property Berbasis Web dengan Pendekatan Rapid Application Development (RAD) - Ivan H. Primananda; Nurudin Santoso; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The property business in Indonesia is one of the businesses that has experienced significant development. This is evidenced by the many new housing developments at competitive prices. Kupang City is the capital and administrative center of the Nusa Tenggara Timur (NTT) province, Indonesia. Based on data from the Central Statistics Agency of NTT Province, the increase in the population in NTT has increased by 2.07%. But in reality many prospective property buyers are still confused to buy a house by using a mortgage (KPR) because they do not know the amount of funds to be paid every month and also the difficulty of having to survey the state of the house one by one makes the prospective buyers overwhelmed to look for addresses from home sales agent. To solve this problem, the Land and Property Marketplace System is developed which is expected to facilitate potential buyers and investors in selecting, surveying and obtaining information related to the property to be purchased. The Land and Property Marketplace Systems provide the main features such as agent registration, property registration, KPR simulation, KPR info and also direct comment and chat features between potential buyers and property agents. The Land and Property Marketplace System will be implemented with the Laravel framework using the PHP programming language and JavaScript on the backend side and PhpMyAdmin as a database used to store data. This system produces 20 functional needs and 1 non-functional needs, and found 3 actors is agent, customer, and guest. The system tests using unit testing with the white box method and validation testing with the black box method obtained 3 unit tests and 27 validation tests with 100% valid results. Then the system complimented with compatibility testing using SortSite's software to request system robustness if requested in various web browsers and obtain 100% valid system results in various web browsers.